Neuroscience and mathematics - Pérez Mendoza, Elizabeth del Pilar (2018)
Mathematics, in addition of being useful, it is extremely necessary for interacting fluently and effectiveness in a “mathematized” world. The majority of these daily activities require of decisions based on this science, for example, choosing the best option of buying a product, understanding the graphics of newspapers or the best options of investment, as well as interpreting the environment, daily objects, masterpieces. The need of mathematics knowledge grows everyday as its application in several professions.